Protection of Medical Personnel in Armed Conflict: A Review of the Provisions of International Criminal Law - Eka Priyanto; Ery Rachma Firsanti; Tri Agus Haryono (PT FORMOSA CENDEKIA GLOBAL, 2024)
The protection of medical personnel in armed conflict is an important issue in international criminal law. This article provides an overview of the provisions governing such protection. This review covers various aspects, from the definition of medical personnel to the protection afforded in conflict situations. This research uses document analysis methods to collect data from various sources such as international conventions, agreements and other legal documents. It is hoped that the findings of this research will provide a better understanding of the protection of medical personnel in the context of international criminal law